(untitled) (Research, Society and Development, 2022)
Objective: describe existing smartphone applications within the health area, discussing their contributions to the health sector and quality of life. Method: descriptive study conducted through an integrative review in lilacs, medline, collect SUS, bdenf - nursing and SciELO databases. The inclusion criteria adopted were the complete articles published in Portuguese; addressing the theme of the use of mobile applications in the area of health, within the period 2017 to 2022. Results: 38 works participated in this review, being 29 articles, 8 dissertations and a thesis, thus evidencing the use of technologies in various themes related to health processes. Conclusion: Mobile apps have significant health care benefits for patients, their families, and health professionals. It is possible to recognize the good acceptance of customers in relation to technological innovations as an aid in the processes of prevention, promotion, assistance and health monitoring.